(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO. 1. Premessa - 2. L’episcopalis audientia. Riconoscimento, evoluzione e problematiche - 3. L’età medievale e la nascita degli officiali. I tribunali “guardiani del vincolo” - 4. Dal Concilio di Trento alla prima codificazione - 5. Dal Codex del 1983 all’Istruzione Dignitas connubii - 6. Conclusioni. Ipse Episcopus iudex: return to the canonical tradition? ABSTRACT: The new procedural norms for marriage nullity approved by Pope Francis invested the diocesan Bishop with a peculiar role, adding to his previous duties in the judicial sphere that to judge personally in the new processus brevior. Bishops have always been considered the “natural judges” in their dioceses, but this task was previously exercised by appointing the tribunal staff and supervising the judicial activity. Some Authors have affirmed - referring, for example, to the ancient episcopalis audientia - that with this reform a longtime practice of the Church was restored. However, a more accurate study of the evolution of the episcopal potestas iudicandi through the centuries reveals a progressive and conscious devolution of its daily exercise to specialized clerics and colleges, exclusively dedicated to their functions. This trend, transposed in the 1917 Code of Canon Law and confirmed in the present Code promulgated after the Second Vatican Council, has been lastly strengthened in the Instruction Dignitas connubii approved by John Paul II.